2023
DOI: 10.1108/ijlm-11-2022-0457
|View full text |Cite
|
Sign up to set email alerts
|

What does “sustainable supply chain management” really mean? A contribution to bridging the gap between research, education and practice

Abstract: PurposeThis study explores practitioners' perspectives on and definitions of sustainable supply chain management (SSCM), which are then compared to academic definitions to identify new implications for researchers, educators and practitioners.Design/methodology/approachAn abductive, explorative and qualitative approach was followed in the form of a review and classification of 31 academic definitions of SSCM as well as 30 interviews with supply chain (SC) practitioners.FindingsThe practitioners' answers show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Sustainable supply chain management refers to several concepts such as "closed-loop supply chains", "responsible sourcing", "green logistics", and "performance measurement"; however, a consistent definition is still needed [153,154]. Usually used for the integration of economic, environmental, and social aspects into supply chain management to increase performance and manage risks from environmental and social practices along the supply chain, the social dimension has received less attention in existing studies [155]. Similarly, sustainable supply chain management has received less attention from professionals who have another understating and definition of this concept compared to scholars.…”
Section: Strategic Supply Chain Pedagogical Activities and Teaching I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable supply chain management refers to several concepts such as "closed-loop supply chains", "responsible sourcing", "green logistics", and "performance measurement"; however, a consistent definition is still needed [153,154]. Usually used for the integration of economic, environmental, and social aspects into supply chain management to increase performance and manage risks from environmental and social practices along the supply chain, the social dimension has received less attention in existing studies [155]. Similarly, sustainable supply chain management has received less attention from professionals who have another understating and definition of this concept compared to scholars.…”
Section: Strategic Supply Chain Pedagogical Activities and Teaching I...mentioning
confidence: 99%
“…In the same vein, ref. [155] concluded that practitioners show limited awareness of supply chain challenges beyond their firms, emphasizing economic and environmental concerns. They highlight understudied areas in sustainable supply chain management, such as human resources, leadership for sustainability, and ethics, indicating the need for further exploration.…”
Section: Strategic Supply Chain Pedagogical Activities and Teaching I...mentioning
confidence: 99%